Prevalence and prognostic value of sarcopenia in patients with bladder cancer undergoing radical cystectomy: a systematic review and meta-analysis - Zhang, Lei; Li, Fanmin; Liu, Lemei; Cao, Jianjia; Yang, Xiye (Frontiers in Oncology, 2025)
BackgroundThe relationship between sarcopenia and clinical outcomes in patients with bladder cancer (BC) has been inconsistently reported in the literature. Some studies have identified sarcopenia as a potential prognostic indicator associated with reduced survival following radical cystectomy (RC).ObjectivesThis study was conducted to systematically evaluate the prognostic significance of sarcopenia in patients with bladder cancer undergoing RC.DesignSystematic review and meta-analysis.MethodsWe conducted a comprehensive search of multiple databases, including PubMed, EMBASE, Web of Science, Cochrane Library, CHINAHL, China National Knowledge Infrastructure (CNKI) Databases, and Wanfang Database, up to August 23, 2023, to identify both retrospective and prospective cohort studies. To assess the methodological quality of the included studies, the Newcastle-Ottawa Scale was utilized to evaluate the risk of bias. Furthermore, heterogeneity and potential publication bias were examined, and both subgroup and sensitivity analyses were performed to ensure the robustness of the findings.ResultsA total of 18 studies comprising 3,110 patients were included in the quantitative synthesis. The results of meta-analysis showed that the pooled prevalence of sarcopenia was estimated to be 49% (95% CI: 41% to 57%, I2 = 95.3%, P < 0.001), which was based on a random-effects model. We observed that BC patients with sarcopenia had a worse OS (HR:1.64, 95% CI: 1.30 to 1.97, I2 = 76.5%, P < 0.001} and CSS (HR:1.86, 95% CI: 1.45 to 2.27, I2 = 0.0%, P < 0.001).ConclusionSarcopenia is commonly observed among patients with bladder cancer and appears to be an important prognostic indicator associated with decreased OS and CSS in those undergoing radical cystectomy. Further prospective studies are warranted to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023456724.